Transfer and Expression of Foreign Genes in Mammalian Cells. (August 2000) - Colosimo, A.; Goncz, K.K.; Holmes, A.R.; Kunzelmann, K.; Novelli, G.; Malone, R.W.; Bennett, M.J.; Gruenert, D.C.
The transfer of foreign genes into eukaryotic cells, in particular mammalian cells, has been essential to our understanding of the functional significance of genes and regulatory sequences as well as the development of gene therapy strategies. To this end, different mammalian expression vector systems have been designed. The choice of a particular expression system depends on the nature and purpose of the study and will involve selecting particular parameters of expression systems such as the type of promoter/enhancer sequences, the type of expression (transient versus stable) and the level of desired expression. In addition, the success of the study depends on efficient gene transfer. The purification of the expression vectors, as well as the transfer method, affects transfection efficiency. Numerous approaches have been developed to facilitate the transfer of genes into cells via physical, chemical or viral strategies. While these systems have all been effective in vitro they need to be optimized for individual cell types and, in particular, for in vivo transfection.